Computational code development for parameterized study in the calculation of the thermal load in a refrigerating chamber - Moreira, José Luciano Batista (2021)
Cold rooms are fundamental equipment for the preservation of perishable foods, guaranteeing the maintenance of the quality of products in the stages of their processing and distribution. The correct dimensioning of this equipment represents efficiency related to the cooling and freezing performance, as well as the energy efficiency of the system. This project deals with the development of a computational code on the EES platform (Engineering Equation Solver) to determine the energy consumption of the evaporator unit (thermal load) of a cold room. The study presents parameterized results for the thickness of the thermal insulation and the inlet temperature of the products. It was verified that the discrepancy between the maximum and minimum operation regimes of the cold room, represents a reduction of approximately 20,19% of the energy consumption of the evaporator unit. Thus, it can be concluded that the parameterized study can result in a diagnosis of energy savings for cold storage projects.